Meta Analysis the Effect of Intervention Based School toward Nutrition on Body Mass Index - Wulandari, Wulandari; Dewi, Yulia Lanti Retno; Murti, Bhisma (Journal of Epidemiology and Public Health, 2021)
Background: Body mass index (BMI) is a metric used to define anthropometric characte